2023
DOI: 10.56294/dm202324
|View full text |Cite
|
Sign up to set email alerts
|

Thematic Specialization of Institutions with Academic Programs in the Field of Data Science

Abstract: Introduction: data science careers are on the rise due to the growing demand for technical skills in this area. Data science careers focus on collecting, organizing, and analyzing data to identify patterns and trends, which allows organizations to make informed decisions and develop effective solutions. Aim: to analyze the thematic specialization of institutions with academic programs in the area of data science. Methods: The Scopus database was used to conduct a bibliometric analysis aimed at examining the th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
0
5
0
1
Order By: Relevance
“…Some authors consider collective intelligence as a common type of collective intelligence. (18,42) They outlined its role in facilitating innovation, decision-making, and problem-solving. Whereas, other authors refer to crowdsourcing as a form of open innovation that enhances a firm's innovative capabilities.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors consider collective intelligence as a common type of collective intelligence. (18,42) They outlined its role in facilitating innovation, decision-making, and problem-solving. Whereas, other authors refer to crowdsourcing as a form of open innovation that enhances a firm's innovative capabilities.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of the development of ICT and its inclusion in pedagogical practices, ubiquitous education emerges, aiming to incorporate more accessible learning for students in their immediate environments. 45,[47][48][49] On the other hand, the most relevant institution in terms of the number of publications was the CNRS Centre National de la Recherche Scientifique, with thirty-nine publications. Additionally, the United States ranks first in scientific production with 21%, with English as the predominant language in most publications (96%).…”
Section: Discussionmentioning
confidence: 99%
“…Among these algorithms, it has been observed that RandomForest has exhibited the best performance, achieving an accuracy of 99% (Table 03). Next, we will discuss the theoretical rationale behind why RandomForest has outperformed other algorithms [50][51][52][53][54] .…”
Section: Sample Selection Processmentioning
confidence: 99%